2006
DOI: 10.1177/039139880602900705
|View full text |Cite
|
Sign up to set email alerts
|

Minimized Weight Gain between Hemodialysis Contributes to a Reduced Risk of Death

Abstract: After a prolonged period of 24 months the extent of ultrafiltration need seems to be important for the outcome of the patients. Thereby those with higher need of ultrafiltration had worse prognosis. It seems important to motivate patients to reduce the extent of fluid intake between dialysis to prolong survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 13 publications
3
28
0
3
Order By: Relevance
“…Of note, we lacked data on interdialytic weight gain, which may influence decisions on session length and may also be directly related to mortality and morbidity. However, inasmuch as patients with larger interdialytic weight gains are more likely to have longer session lengths and are more likely to die,3033 any bias would be toward the null and would not explain our findings. In addition, we tracked prescribed (not delivered ) session length.…”
Section: Discussionmentioning
confidence: 78%
“…Of note, we lacked data on interdialytic weight gain, which may influence decisions on session length and may also be directly related to mortality and morbidity. However, inasmuch as patients with larger interdialytic weight gains are more likely to have longer session lengths and are more likely to die,3033 any bias would be toward the null and would not explain our findings. In addition, we tracked prescribed (not delivered ) session length.…”
Section: Discussionmentioning
confidence: 78%
“…These findings could have widespread implications in the treatment of patients with ESRD undergoing HD, considering that IDH is estimated to occur in 20%-30% of all dialysis treatments (depending on the definition used for IDH) (4), and that IDWG has been shown to increase the risk of CV events and mortality (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…This was associated with greater interdialytic weight gains. Studies have reported that limiting interdialytic weight gain is associated with improved survival in haemodialysis patients [19]. …”
Section: Discussionmentioning
confidence: 99%